Is It Too Late? Exploring Self-Actualisation of a Self-Proclaimed Artist in a Restrictive Chinese-Indonesian Family - Erick Setiawan Santoso; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2020)
Self-actualisation is an interesting topic to be talked about in Indonesia, as Indonesian families still uphold filial piety very highly. Thus, the concept of putting forwards one’s dreams and wishes for one’s own future and brushing aside one’s parents’ wants and plans is mostly unheard of. I made this creative work, in form of a novel, to highlight this highly-relevant phenomena and initiate the talk between parents and their descendants. This story is written from the perspective of the son of a family who wants to be an artist, but faces hurdles in the form of his chasing tiger mother and how that affected him and his decision-making in relation of becoming the best version of himself.Keywords: Artistry, Chinese-Indonesian, Filial piety, Poetry, Realistic fiction, Self-actualisation.